2009
DOI: 10.1039/b819301k
|View full text |Cite
|
Sign up to set email alerts
|

Influence of amine ligands on the aquation and cytotoxicity of trans-diamine platinum(ii) anticancer complexes

Abstract: Three (15)N-labelled trans-Pt(ii) amine complexes with isopropylamine ((15)N-ipa), methylamine ((15)N-ma) and dimethylamine ((15)N-dma) have been prepared and characterized. 2D [(1)H,(15)N] HSQC NMR spectroscopy was used to obtain the rate and equilibrium constants for the aquation of trans-[PtCl(2)((15)N-ipa)((15)N-ma)] ((15)N-1), trans-[PtCl(2)((15)N-dma)((15)N-ma)] ((15)N-2) and trans-[PtCl(2)((15)N-dma)((15)N-ipa)] ((15)N-) in 100 mM NaClO(4) solutions at 298 K. New (15)N shift ranges for H(2)N-Pt(II)-N an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 35 publications
3
41
0
2
Order By: Relevance
“…Trans,trans,trans-[PtCl 2 (OH) 2 (dma)(ipa)], 1, and trans-[PtCl 2 (ipa)(ma)], 2, were prepared using previously described procedures [24,25]. Guanosine-5′-monophosphate (GMP), cytidine-5′-monophosphate (CMP) and 9-methyladenine (9MeA) were purchased from Sigma-Aldrich and adenosine-5′-monophosphate (AMP) from Acros Organic.…”
Section: Methodsmentioning
confidence: 99%
“…Trans,trans,trans-[PtCl 2 (OH) 2 (dma)(ipa)], 1, and trans-[PtCl 2 (ipa)(ma)], 2, were prepared using previously described procedures [24,25]. Guanosine-5′-monophosphate (GMP), cytidine-5′-monophosphate (CMP) and 9-methyladenine (9MeA) were purchased from Sigma-Aldrich and adenosine-5′-monophosphate (AMP) from Acros Organic.…”
Section: Methodsmentioning
confidence: 99%
“…Early structure-activity relationship studies suggested that transplatin complexes would be inactive as antitumour drugs [14]. However, more recent studies, resulting in part from the search for drugs which are active against cisplatin-resistant tumours, have reactivated an interest in trans-isomers [15][16][17][18][19]. Thus, there have been promising reports of trans-platinum complexes containing planar amines [20][21][22] or bulky amine ligands [23,24] which showed cytotoxicity against human tumour cell lines equal to or higher than cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…What seems surprising is that this complex is also the less aquated in the equilibria, despite the faster aquation, the amount of monoaqua species is lower. If we think that, in general, the most active species is the monoaquo and more importantly, trans-PtCl 2 (ma)(dma) the most cytotoxic of the series in the cell lines checked [25], we can end in that the lower concentration of monoaquo species in the equilibrium must be an advantage. Our interpretation is that this situation favors the monoaquo species not to be kidnapped and erased from the milieu by any molecule before it gets the target.…”
Section: Speciation Of Trans Complexes In Water Solution and Its Aftementioning
confidence: 98%